Influence of external distortions on multifactor optical identification tags with photoncounting - A. Mohammed, Emad (University of Thi-Qar Journal of Science, 2015)
The multifactor optical ID tag reinforces high security verification purposes for credit cards, passports, and productidentification marks. In this applications, the optical ID tag should be robust to external distortions. In this work, weinvestigate the robustness to external distortions of multifactor optical identification (ID) tag based on multifactoroptical encryption authentication (MOEA) method, binarization method, and photon counting (PC) technique. Theexternal distortion caused by a uniform and non uniform occlusion (cropping and scratches) of some pixels of theproposed optical ID tags is investigated. Computer simulations are presented to test the system performance against these types of distortions. The results illustrated that the system is able to validate the ID tags, even under severe distortion and it confirmed that the proposed BPOID tag based on PC-MOEA method is more robust compared with the traditional ID tags to such as cropping and scratches.